Socialist Licenses? A Rejoinder to Michel Bauwens and Vasilis Kostakis - Stefan Meretz (tripleC: Communication, Capitalism & Critique)
This article is a critical reflection on Michael Bauwens and Vasilis Kostakis’ paper “From the Communism of Capital to Capital for the Commons: Towards an Open Co-operativism” (tripleC 12 (1): 356-361)